Pengaruh Profitabilitas, Leverage dan Kualitas Audit Terhadap Penghindaran Pajak: (Studi Empiris pada Perusahaan Sektor Transportasi dan Logistik yang Terdaftar di Bursa Efek Indonesia Periode 2020 - 2024) - Simon Lois Pernando Sihombing; Melan Sinaga (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2026)
This study aims to examine the effect of profitability, leverage, and audit quality on tax avoidance in companies within the transportation and logistics sector. The research was conducted using data from transportation and logistics companies listed on the Indonesia Stock Exchange (IDX) over the 2020–2024 period. A purposive sampling method was employed, resulting in a sample of 25 companies that met the research criteria. Data analysis was carried out using multiple linear regression, processed through SPSS software version 22.0. The results show that leverage has a negative and significant effect on tax avoidance, suggesting that companies with higher levels of leverage are less likely to engage in tax avoidance practices. On the other hand, profitability and audit quality do not significantly affect tax avoidance. This indicates that while financial performance and the quality of audits may influence various corporate practices, they do not have a direct impact on tax avoidance behaviors in the transportation and logistics sector. The findings contribute to the understanding of tax avoidance determinants and provide insights for policymakers and practitioners in the field of corporate finance and taxation.